An analytical approach to modelling shear panels in steel beams at elevated temperatures. (15th February 2015) - Quan, Guan; Huang, Shan-Shan; Burgess, Ian
Graphical abstract: Highlights: Theoretical model to investigate shear buckling of Class 1 beams in fire. Shear buckling occurs mainly in short beams. For long beams, bottom flange buckling happens instead. Shear resistance reaches its peak when plastic buckling starts. In post-buckling shear resistance of the panel decreases. Abstract: Shear buckling of beam webs in the vicinity of beam-to-column connections has been observed in many full-scale fire tests. This phenomenon can lead to force redistribution within the adjacent connections, and even influence the performance-based analysis of full-scale structures in fire. However, beam-web shear buckling for Class 1 beams at either ambient or elevated temperatures has not been well studied previously. In this work an analytical model has been created to predict the shear buckling behaviour of Class 1 beams in the vicinity of beam-to-column connections at ambient and elevated temperatures. The model considers the reduction of resistance of the beam after web shear buckling has occurred. It is capable of predicting the shear resistance and transverse drift of the shear panel from its initial loading to final failure. Several 3D finite element models have been created using the ABAQUS software, in order to validate the analytical model over a range of geometries. Comparisons between the theoretical and FE models have shown that the proposed method provides sufficient accuracy to be implemented and used in performance-based global modelling.